Work-Family Conflict dan Parenting Self- Efficacy pada Ibu Bekerja di Jakarta - Dara Aprilia Christianty; Wieka Dyah Partasari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2021)
The aim of this research is to identify the relationship between work-family conflict and parenting self-efficacy among working mothers in Jakarta. The research is a quantitative with correlational research design. Participants for this research is consisted by 121 mothers with the range of aged 23 to 56 years old, live with working husband and the children, have child aged below 18 years old, and have full-time job in Jakarta. Data were collected using two measurement tools are Work-Family Conflict Scale (WFCS) and Self-Efficacy for Parenting Task Index (SEPTI). The data was measured using Spearman correlation and it has been showed there is the relationship between work-family conflict and parenting self-efficacy significantly (rs = -0.387, p = 0.000 (p < 0.01)). These two variables are negatively related to each other. It can be concluded who working mothers have low their work-family conflict, they have high self-efficacy to fulfill their role as parent. The recommendation for future research will do in qualitative research to know how the parents, father and mother, take care of their children and what kind of social support that has been accepted for working mothers. Keywords: Work-Family Conflict, Parenting Self-Efficacy, Working Mothers